Cementing Without Trialing is Safe and Efficient for Hip Hemiarthroplasty - Hari P. Bezwada, MD; Dilan Prasad, BS; Carter Levine, BS (Arthroplasty Today, 2025)
Displaced femoral neck fractures most commonly occur in elderly patients as the result of low energy injuries. Surgical interventions for these fractures have included either bipolar or unipolar hip hemiarthroplasty. Furthermore, these procedures may be performed with either cemented or cementless implants. Despite compelling data suggesting lower reoperation rates and better outcomes with cemented implants, many surgeons still use cementless implants in these elderly patients according to registry data from the American Joint Replacement Registry. Additionally, the direct anterior approach has become increasingly popular as a surgical approach for hip arthroplasty. We describe an efficient surgical technique for cemented hemiarthroplasty via the direct anterior approach. In this technique, head trialing is only done after the stem is cemented, thereby reducing the risks of intraoperative fracture to an already osteoporotic bone.